2016
DOI: 10.1111/hae.12932
|View full text |Cite
|
Sign up to set email alerts
|

Declining trends in invasive orthopedic interventions for people with hemophilia enrolled in the Universal Data Collection program (2000–2010)

Abstract: Introduction Recurrent joint hemarthroses due to hemophilia (Factor VIII and Factor IX deficiency) often lead to invasive orthopedic interventions to decrease frequency of bleeding and/or to alleviate pain associated with end-stage hemophilic arthropathy. Aim Identify trends in invasive orthopedic interventions among people with hemophilia who were enrolled in the Universal Data Collection (UDC) program during the period 2000–2010. Methods Data were collected from 130 hemophilia treatment centers in the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The reported frequency of joint bleeding in women respondents in B‐HERO‐S with moderate and “low” mild hemophilia (FIX 6%‐20%) suggests that additional characterization of bleeding and arthropathy in women with FIX deficiency is needed. B‐HERO‐S findings regarding joint disease support prior US epidemiologic assessments showing joint disease and joint surgeries do occur in patients with mild‐moderate hemophilia and in women, including symptomatic carriers . FIX activity levels should be checked in all women known or suspected to be carriers, regardless of the presence of joint or bleeding complaints.…”
Section: Discussionmentioning
confidence: 54%
“…The reported frequency of joint bleeding in women respondents in B‐HERO‐S with moderate and “low” mild hemophilia (FIX 6%‐20%) suggests that additional characterization of bleeding and arthropathy in women with FIX deficiency is needed. B‐HERO‐S findings regarding joint disease support prior US epidemiologic assessments showing joint disease and joint surgeries do occur in patients with mild‐moderate hemophilia and in women, including symptomatic carriers . FIX activity levels should be checked in all women known or suspected to be carriers, regardless of the presence of joint or bleeding complaints.…”
Section: Discussionmentioning
confidence: 54%
“…The Universal Data Collection (UDC) program, in collaboration with federally supported haemophilia treatment centers (HTCs) across the United States of America, included data from people with bleeding disorders who have undergone an invasive orthopaedic intervention. This project builds on previous work within the UDC which looked at outcomes in IOI in the ankle and the rates of invasive orthopaedic interventions …”
Section: Introductionmentioning
confidence: 99%
“…project builds on previous work within the UDC which looked at outcomes in IOI in the ankle 11 and the rates of invasive orthopaedic interventions. 12 The purpose of our study was to identify risk factors associated with IOIs performed in males with haemophilia enrolled in the UDC surveillance program from 2000 until 2010. The hypotheses that the authors held for the project were as follows: (i).…”
mentioning
confidence: 99%
“…More recently, epidemiologic studies have found that the risk of joint bleeding does not always predictably align with categories of hemophilia severity; furthermore, while bleeding risk is reduced with increasing factor activity, joint bleeding can occur in some individuals even with mild hemophilia and factor activity levels of up to 12% to 20% . These findings are not altogether surprising, as multiple long‐term registries have shown an impact of hemophilia on joint function and an occasional need for joint procedures in people with mild and moderate hemophilia . Thus, obtaining a deeper understanding of the psychosocial impact of hemophilia on individuals and their families across the spectrum of mild/moderate and severe disease is critical in elucidating unmet needs in the population to inform improvements in comprehensive care.…”
mentioning
confidence: 99%
“…3,8,9 These findings are not altogether surprising, as multiple longterm registries have shown an impact of hemophilia on joint function and an occasional need for joint procedures in people with mild and moderate hemophilia. 10 Following this summit, working groups within individual HERO study countries continued to analyze the study data and consider gaps that could be addressed through advocacy and educational initiatives.…”
mentioning
confidence: 99%